Adaptasi Masyarakat dalam Menghadapi Gejala Perubahan Iklim di Wilayah Pesisir Kota Bandar Lampung - Pratiwi, Fennidya Nur; Asbi, Adnin Musadri; Kurnianingsih, Nela Agustin (REKSABUMI, 2025)
Climate change significantly impacts coastal areas, including Bandar Lampung City, which has experienced rising temperatures, decreasing rainfall, and more frequent tidal flooding. This study aims to analyze the forms of adaptation undertaken by coastal communities in response to climate change symptoms and to evaluate their level of understanding and adaptive responses. A mixed-methods approach with a deductive framework was used, involving primary data collection through questionnaires and interviews, as well as secondary data from literature and institutional documents. The results show that while most residents understand the symptoms of climate change, only a small portion have implemented appropriate adaptation measures. These include energy conservation, drainage improvement, stilt house construction, and mangrove preservation. A gap exists between knowledge and action, influenced by social perceptions, education level, and government support. The findings underscore the importance of strengthening community-based adaptive capacity and integrating spatial risk data such as InaRISK into local climate resilience strategies.